Peran dan Strategi Pembinaan Bahasa Arab LPTQ Jawa Timur bagi Peserta MTQ Cabang Qiraat Murattalah - Anindya, Fawwaz Talitha; Yusuf, Kamal (Jurnal Al-Mashadir: Journal of Arabic Education and Literature, 2025)
This study aims to analyze the role of Lembaga Pengembangan Tilawatil Qur'an (LPTQ) East Java in enhancing Arabic language mastery among participants of Musabaqah Tilawatil Qur'an (MTQ) in Qiraat Murattalah branch. The research examines coaching strategies employed and implementation challenges faced. Using qualitative descriptive approach, data collection involved in-depth interviews, Google Form questionnaires, and indirect observation through YouTube coaching videos. Results indicate LPTQ plays strategic role through drilling methods, mentoring systems, and performance examinations emphasizing tajweed, fashahah, and voice mastery. Main challenges include mother tongue interference, limited training time, weak Arabic foundation, and regional competency gaps. This research confirms the importance of systematic coaching in Arabic language mastery as foundation for eloquent Quranic recitation.